Flux closure during a substorm observed by Cluster, Double Star, IMAGE FUV, SuperDARN, and Greenland magnetometers - Milan, S. E.; Wild, J. A.; Hubert, B.; Carr, C. M.; Lucek, E. A.; Bosqued, J. M.; Watermann, J. F.; Slavin, J. A. (Annales Geophysicae, 2006)
We examine magnetic flux closure during an extended substorm interval on 29 August 2004 involving a two-stage onset and subsequent re-intensifications. Cluster and Double Star provide observations of magnetotail dynamics, while the corresponding auroral evolution, convection response, and substorm current wedge development are monitored by IMAGE FUV, SuperDARN, and the Greenland magnetometer chain, respectively. The first stage of onset is associated with the reconnection of closed flux in the plasma sheet; this is accompanied by a short-lived auroral intensification, a modest substorm current wedge magnetic bay, but no significant ionospheric convection enhancement. The second stage follows the progression of reconnection to the open field lines of the lobes; accompanied by prolonged auroral bulge and westward-travelling surge development, enhanced magnetic bays and convection. We find that the tail dynamics are highly influenced by ongoing dayside creation of open flux, leading to flux pile-up in the near-tail and a step-wise down-tail motion of the tail reconnection site. In all, 5 dipolarizations are observed, each associated with the closure of ~0.1 GWb of flux. Very simple calculations indicate that the X-line should progress down-tail at a speed of 20 km s-1, or 6 RE between each dipolarization.